Use of maleic hydrazide (MH) to induce branches in maiden fruit trees - L. S. Jankiewicz; J. Kozyra (Acta Agrobotanica, 2015)
MH as a single spray in concentrations 700 -1500 mg/l was used in July to induce premature offshoots in nursery trees. The trees of pear, plum and of 3 apple cultivars showed little or no response to MH treatment Due to this treatment, however, the trees of 7 other apple cultivars formed 3-5 branches longer than 20 cm, possessing large crotch angles. The growth of the main axis was only temporarily inhibited by the MH treatment.